Iliopsoas Haematoma Presenting with Femoral Neuropathy during Anticoagulation Therapy with Warfarin - Jayaprakash H, Rajesh Kishan Rao, Girish Basappa, (International Journal of Innovative Research in Medical Science, 2018)
Iliopsoas haematoma is a rare complication of anticoagulation therapy, presents with sudden onset of groin or flank pain, with or without neurological manifestation of the lower extremity due to femoral neuropathy. Computed Tomography of abdomen and pelvis is the most useful tool for diagnosis. Treatment options are conservative therapy, surgical decompression, ultrasound guided percutaneous drainage or trans-catheter arterial embolisation. We report a case of iliopsoas haematoma, in a 28 years old male, post aortic valve replacement on oral anticoagulation therapy, presenting with right groin and flank pain with paraesthesia of right lower limb.